Stakeholders’ perceptions of sustainable development of higher education institutions: an intellectual capital approach - Pedro, Eugénia de Matos (2020)
Abstract Purpose – This study aims to identify stakeholders’ perceptions of the effects associated with different components of intellectual capital (IC) on the sustainable development (SD) practices of higher education institutions (HEIs). Design/methodology/approach – The empirical approach uses a structural equation model to provide new empirical findings in relation to 738 students and 587 lecturers/researchers at seven Portuguese state HEIs through quantitative research. Findings – The results obtained are, firstly, important contributions to the literature on the IC and SD practices of HEIs, as a relationship between these two constructs is confirmed, especially through relational capital (RC) and structural capital (SC). Secondly, the stakeholders considered show different perceptions of the influence of the components of HEIs’ IC on these institutions’ SD practices, and thirdly, perception of the economic dimension is most influenced. Practical implications – The empirical findings indicate the need to provide better information about HEIs’ policies and practices of SD and how the latter contribute to the SD of the institution and its region of influence. Originality/value – No previous studies investigate students and teachers/researchers’ perceptions of the social, environmental, economic and organizational dimensions of SD in HEIs and at the same time how those perceptions can be influenced by the components of IC (e.g. human capital, SC, RC) in that institution.